Refusal of claimant from claim: legal nature and consequences of implementation - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2019)
The article analyzes the legal nature of the plaintiff’s refusal to sue. The author believes that the refusal of the claim cannot be identified with the refusal of the plaintiff from his material rights. Refusal of the claim represents a refusal of the claimant only from the further continuation of the process. Such a refusal only in that case may prevent the plaintiff from reapplying to the court if he was involved with simultaneous acknowledgment of the plaintiff of his wrongfulness in the dispute. On this basis, the author makes proposals for the further improvement of civil procedural law, in particular, proposes to introduce rules on it to withdraw the claimant’s statement of claim.
Keywords: civil process; plaintiff; waiver of the claim; waiver of material rights; withdrawal of claim